Effect of Optical Signal Beam Shift on the Performance of Satellite Chaos Laser Safety Communication System under Space-Integrated-Ground Information Network - Mi LI; Qiang CHEN; Cheng ZENG; Xue WANG; Yisi WANG; Xiangfei CHEN (天地一体化信息网络)
The eff ect of beam center shift on the performance of satellite chaos laser safety communication system in spaceintegrated-ground information network was studied, the bit error rate (BER) formulae with external and internal mismatch caused by beam center shift was conducted.Based on the BER formulae, the eff ect of beam center shift on external and internal mismatch and system performance was analyzed.The results show that beam wander will further increase external and internal mismatch based on pointing error then aff ect system performance.When pointing error is relatively small, optimizing beam wander will improve system performance more, and when pointing error is relatively large, optimizing internal mismatch will improve system performance more.The research results of this paper have important reference signifi cance for the actual engineering design of satellite chaos laser safety communication system, and lay the foundation for the promotion of terrestrial high-speed chaos laser safety technology to the fi eld of space-integrated-ground.